A FVNexA whatsapp e a retextualização na oralidade: contação de história na educação infantil - Medeiros, Julieta Vilar (2023)
In the present investigation, it was aimed to contribute to current debates about the use of technology and textual genres in Early Childhood Education and reflect on pedagogical practices based on digital tools that are already used in children's daily lives in their social practices outside the classroom. To develop the investigation, it was set out the following general objective: to investigate whether the use of the virtual tool WhatsApp in retextualization activities from orality to writing in Early Childhood Education, based on the application of a Didactic Sequence, would be viable and productive in the school environment. For the study, it was used, as a theoretical contribution, the authors: Schneuwly and Dolz (2004), Koch and Elias (2006), Marcuschi (2007; 2008; 2010), Rojo (2012), Travaglia (2013), Coscarelli (2016), Matos (2020), among others. We collected and analyzed data based on literature review, observation, and application of didactic sequences. The research, divided into 4 chapters, reveals the applicability of the FVNexA WhatsApp in retextualization activities in Early Childhood Education. Furthermore, it shows that the use of the tool for oral recording of story retelling facilitated the teacher's work as a scribe. Therefore, we observed that using the FVNexA WhatsApp in the retelling preserved the children's spontaneity and enabled fluency and coherence in the story's plot.